Who is Interested in Carpooling and Why: The Importance of Individual Characteristics, Role Preferences and Carpool Markets. Issue 8 (December 2018) - Park, Yujin; Chen, Na; Akar, Gulsah
Carpooling is an informal form of commuter ride-sharing that can mitigate traffic congestion and parking demand. While ride-sharing and carpool formation require both a driver and at least one passenger, there has been a lack of studies that explore potential users of carpooling and their role preferences (driver versus passenger); perceived incentives, attitudes and current mode choices may affect their willingness to carpool and their role preferences. This study examined the factors affecting individuals' carpooling decisions and carpool role preferences using data from Ohio State University's 2012 Campus Travel Pattern Survey. Based on individuals' stated interests and choices, three market segments were identified: current carpool users, potential carpool users, and not-interested commuters. The analyses revealed that incentives and deterrents to carpooling significantly differ by role preference. People favoring the passenger role emphasized safety, flexibility and parking cost-savings, whereas those favoring the driver role tended to find value in the convenience and opportunities for socializing through a carpool trip. People receptive to both roles emphasized flexibility and all types of cost reductions. Although most people did not elect technological aids as a meaningful intervention, potential carpool users, particularly those favoring the passenger role, were more likely to seek these aids. Using probit and bivariate probit regressions, carpool interest and choice were found to be associated with commute distance, university affiliation, marital status, current travel mode, and personal attitude. Concern for the environment, and the propensity to make stops while commuting were positively associated with both carpooling interest and decision to carpool.